(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In this research, we analyze the language situation in Vinnytsia. Our main research question concerns current Ukrainian-Russian bilingual practices of three generations, the last of whom lives in the city. We examined this question with the method of socio-linguistic survey. The total number of 400 participants represents school students (from 15 to 17 year-old).